PENGARUH METODE PRAKTIKUM GREEN CHEMISTRY TERHADAP HASIL BELAJAR SISWA KELAS VII SMP NEGERI 08 SINGKAWANG PADA MATERI PEMISAHAN CAMPURAN - Deno Hariyadi; Eny Enawaty; Ira Lestari (Universitas Tanjungpura, 2019)
AbstractThe aimed of this research was to determine differences between students’ learning outcomes using green chemistry practicum method and learning outcome of students using demonstration method, and determined the magnitude of the influence of green chemistry practicum method toward student learning outcomes in the matters of separation mixture. This study used a quasi-experimental with nonequivalent control group design. The research sample consisted of VII A class as the control group and VII E class as the experimental group selected by purposive sampling technique. Learning achievement test were used to collect data. Based on final questionnaire and posttest data analysis using the Mann-Whitney U-test (α = 5%), Asymp.Sig (2-tailed) were 0.000 and 0.078 respectively. Based on data analysis showed that there were differences in students’ learning outcomes using green chemistry practicum method and learning outcome of students using demonstration method. The use of green chemistry practicum methods in terms of had an effect of 28.23% on the learning outcomes of class VII students of SMP Negeri 08 Singkawang in the matters of separation mixture. Keywords: Green Chemistry, Learning outcome, Separation Mixture